Hypoxic BMSC-derived exosomal miR-210-3p promotes progression of triple-negative breast cancer cells via NFIX-Wnt/β-catenin signaling axis - Meng Wang; Yi Zheng; Qian Hao; Guochao Mao; Zhijun Dai; Zhen Zhai; Shuai Lin; Baobao Liang; Huafeng Kang; Xiaobin Ma (Journal of Translational Medicine)
Abstract Background Bone marrow mesenchymal stem cells (BMSCs) are a crucial component of the tumor microenvironment (TME), with hypoxic conditions promoting their migration to tumors. Exosomes play a vital role in cell-to-cell communication within the TME. Hypoxic TME have a great impact on the release, uptake and biofunctions of exosomes. This study aims to elucidate the communication between BMSC-derived exosomal miRNA and triple-negative breast cancer (TNBC) in a hypoxic environment. Methods Exosomes were isolated via ultracentrifugation and identified using scanning electron microscopy (SEM), nanoparticle tracking analysis (NTA) and western blot. A range of bioinformatics approaches were used to screen exosomal miRNAs and the target mRNAs of miRNAs and predict the possible signaling pathways. Expression levels of genes and proteins were assessed by quantitative real-time PCR and western blot. Cell proliferation, apoptosis, migration and invasion were analyzed using CCK-8 assay, EDU assay, transwell migration, wound healing assay and invasion assay, respectively. Dual luciferase reporter gene assay was conducted to confirm the binding between miRNAs and the target mRNAs. The impact of hypoxic BMSC-derived exosomal miRNA on TNBC progression in vivo was evaluated using tumor xenograft nude mouse models. Furthermore, the impact of patients’ serum exosomal miRNA on TNBC was implemented. Results Exosomes derived from hypoxic BMSCs promotes the proliferation, migration, invasion and epithelial-mesenchymal transition of TNBC and suppresses the apoptosis of TNBC. The expression of miR-210-3p in BMSC-derived exosomes is markedly elevated in hypoxic conditions. Exosome-mediated transfer of miR-210-3p from hypoxic BMSCs to TNBC targets NFIX and activates Wnt/β-Catenin signaling in TNBC. Deletion of miR-210-3p in hypoxic BMSC-derived exosomes attenuates TNBC in vivo. Additionally, human exosomal miR-210-3p from the serum of TNBC patients promotes TNBC progression. Moreover, we notably observed a marked downregulation of NFIX expression levels in cancerous tissues compared to paracancerous tissues. Conclusions Hypoxic BMSC-derived exosomal miR-210-3p promotes TNBC progression via NFIX-Wnt/β-catenin signaling axis.